Thermodynamics of negative sulfuric acid and nitric acid clusters by electrospray tandem mass spectrometry - Dubien, Danielle (University of Ottawa (Canada), 2003)
Electrospray-ionization tandem mass spectrometry was used to determine the binding energy of HSO4-(H2SO 4)n ions for n up to 4 and NO3-(HNO 3)n ions for n up to 3. The binding energies obtained experimentally are substantially lower than those in the literature except for the values for NO3-(HNO3) and HSO4 -(H2SO4). The geometries of HSO4-(H2SO 4)n and NO3-(HNO3) n for n up to 3 were optimized using the following levels of theory: AM1, HF/3-21G, HF/6-31 + G(d) B3LYP/6-31 + G(d), and B3LYP/6-311 + G(d,p). The values calculated at B3LYP/6-311 + G(d,p) are in fair agreement with those in the literature. For the same order of clustering, sulfuric acid clusters are bound more strongly than the nitric acid analogues. Neutral acid molecules form clusters with core ions via hydrogen bonds. As the number of neutrals increases, the binding energy decreases.
Keywords: Chemistry, Physical.